Assessing the Sustainability of Community Forest Management: A Study of Rani Community Forest, Makawanpur District, Nepal - Ghimire, Pramod (Journal of Sustainability and Environmental Management, 2025)
Community forestry is widely acknowledged as a fundamental aspect of sustainable forest management in Nepal; however, comprehensive evaluation of its sustainability at the local level are still limited. The current study assessed the sustainability of Rani Community Forest in Makawanpur District through a Criteria and Indicators (C&I) framework that included socio-economic and ecological aspects. Four criteria and 30 indicators were used, addressing enabling conditions for forest management, socio-economic and cultural aspects, forest health and vitality, along with forest management and conservation practices. Data were collected through forest inventory, household surveys (n = 81), focus group discussions, and analysis of operational plan. Sustainability indexes were calculated for specific criteria and combined into Overall Sustainability Index (OSI). The findings revealed a moderate level of socio-economic sustainability (SESI = 0.77) and a strong level of ecological sustainability (ESI = 0.82), leading to overall sustainability index of 0.80. Good regeneration condition and growing stock, efficient protective actions, and timely operational plan updates led to enhanced ecological outcomes. However, limited backstopping, and inadequate livelihood diversification beyond timber sales continue to hinder socio-economic sustainability. The findings suggest that although Rani Community Forest is ecologically self-sufficient, enhancing institutional capacity, diversifying livelihoods, and ensuring financial transparency is essential for achieving long-term sustainability. The results emphasize the effectiveness of C&I-based methods for evidence-driven assessment and adaptive management of community forests in Nepal.